Therapeutic potential of young plasma in reversing age-related liver inflammation via modulation of NLRP3 inflammasome and necroptosis - Baba, Burcu; Ceylani, Taha; Teker, Hikmet Taner; Keskin, Seda; Genc, Aysun Inan; Gurbanov, Rafig; Acikgoz, Eda (Springer, 2025)
The phenomenon of inflammaging, characterized by an increase in low-grade chronic inflammation, is closely associated with diseases related to liver dysfunction. This study investigated daily plasma exchange between 5-week-old and 24-month-old Sprague Dawley rats for 30 days, focusing on protein secondary structures, NLRP3 inflammasome, and necroptosis. Conformation changes in protein secondary structures were identified by infrared spectroscopy-based pattern recognition analysis. Liver biopsies with histochemical and immunohistochemical staining were used to assess molecules associated with inflammation, necroptosis and NLRP3 inflammasome complex. Expression levels of NLRP3 components were determined by qPCR. Enhanced random coils, 310 helices, beta-turns, and loop structures were identified in old rats and young rats with old plasma. Young rats and old rats with young plasma displayed higher alpha-helices and beta-sheet structures. Young rats with old plasma showed increased NLRP3, ASC, caspase-1, IL-1 beta, and IL-18 mRNA levels, indicating an inflammatory response. Whereas old rats with young plasma exhibited lower inflammation levels. Histological evaluations revealed that young rats receiving aged plasma showed significantly increased levels of NLRP3, ASC, caspase-1, IL-1 beta, TNF-alpha, VEGFR2, RIPK1, and MLKL immunoreactivity, whereas decreased immunoreactivity in aged rats receiving young plasma. These findings suggest that young plasma reduces NLRP3 inflammasome activation and necroptosis in aged rats.
Keywords: Inflammaging; Plasma exchange; Infrared spectroscopy; Necroptosis; NLRP3 Inflammasome